Multidisciplinary approach to obesity: Aerobic or resistance physical exercise? - Mohamed Ahmed Said; Mohamed Abdelmoneem; Abdullah Almaqhawi; Ahmad Abdel Hamid Kotob; Mohammed Chaab Alibrahim; Iheb Bougmiza (Elsevier, 2018)
Background: An integrated treatment based on dieting, physical training and cognitive-behavioural psychotherapy is an effective tool to reduce obesity and its consequences. However, the feasibility of this approach is problematic. This study aims to compare two multidisciplinary programs used to improve weight loss. Methods: Fifty-two obese individuals were subjected to an Enhanced Lifestyle Counselling associated with, according to their own choice, dieting (N = 11), or dieting + aerobic training (n = 18), or dieting + resistance training program (n = 23). The study experiment spanned 16 weeks divided into two phases. The first phase lasted 04 weeks and was oriented to enhance motivation and establishing changes in behaviours related to dietary and sedentary lifestyle. The second phase lasted 12 weeks and was oriented to add aerobic or resistance training. Body compositions, cardiovascular disease risk factors, and cardio-respiratory fitness were assessed. Results: Data demonstrated that all obesity treatment programs were able to improve all studied variables. Weight loss levels were −6.03 ± 2.08, −10.5 ± 2.33, and −9.37 ± 1.99 kg in Dieting, DAT and DRT groups, respectively. Our results noted also that exercise training could play an important role in reducing obesity and its consequences. Nevertheless, modifications were more important in DRT at the explosivity and muscle strength and in DAT at fat percentage, aerobic capacity, SA, and CVR factors. Conclusion: The current evidence noted that both multidisciplinary weight loss programs were efficient in the treatment of obesity and its comorbidity. Moreover, the use of aerobic exercises was more effective in reducing body fat and improving cardiorespiratory fitness. However, using resistance exercises appeared to be more appropriate to enhance the muscle potential. Keywords: Integrated treatment, Enhanced lifestyle counselling, Dieting, Aerobic training, Resistance training, Obesity